Super-Efficiency of Education Institutions: An Application to Economics Departments - Matthias Gnewuch; Klaus Wohlrabe (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper investigates the efficiency of 188 economics departments around the world using data from RePEc. We go beyond the heavily used data envelopment analysis and utilize partial frontier analysis - specifically order-α and order-m - which addresses some of the drawbacks of the standard efficiency frontier analysis and allows for so-called super-efficient departments. We examine the particularities of these approaches and find that the super-efficient departments are not only the “usual suspects”. Furthermore, standard output rankings are not well correlated with our estimated efficiency rankings, which themselves are rather similar.
Keywords: I21; I23; D61; 330; super-efficiency; economics departments; data envelopment analysis; order-α; order-m; free disposal hull; RePEc